Relationship of Timings and Outcome of Tracheostomy Among Patients Requiring Prolonged Mechanical Ventilation - Muhammad Asim Shafique; Muhammad Amir Nadeem; Muhammad Afzal (Journal of Bahria University Medical and Dental College)
Objective: To assess the indications of tracheostomy among patients requiring prolonged mechanical ventilation and to observe the relationship of the timings and outcome of tracheostomy with age and gender. Study Design and Setting: It was a descriptive study conducted at intensive care unit (ICU) of Department of Otorhinolaryngology at Bahawal Victoria Hospital from January 2017 to December 2018. Methodology: Secondary data was collected with the help of charts of ICU patients in which elective tracheostomy was done to replace orotracheal intubation for mechanical ventilation. Inclusion and exclusion criteria were designed. Clinical record was reviewed for the assessment of indications of the procedure (medical or surgical) along with age and gender distribution. The timing of tracheostomy in these patients with its outcome in terms of decannulation and weaning were recorded. Proforma was used to enter the findings. Finally results were obtained and assessed on SPSS Version 23. Results: Out of total 551 tracheostomies 42(7.6%) were indicated for the patients of ICU requiring prolonged mechanical ventilation. From the 42 mechanical ventilated patients majority had Guillain-Barre syndrome (GBS) 20(47.6%). Twenty six patients were adults (61.9%) and sixteen were children (38%).Twenty four were male patients (57.1%) and eighteen were females (42.8%). The timing of tracheostomy among majority of the patients (40) was from 7-10 days, with mean of 9th day with good outcome. Only two patients who underwent tracheostomy after two weeks had to face poor outcome (failed decannulation, late weaning) (4.7%). Conclusion: Neuroparalytic lesions were the common indication among the patients requiring prolonged mechanical ventilation with tracheostomy. Tracheostomy if performed earlier in such patients carries good outcome.